A Comparison of C4.5 and K-Nearest Neighbor Algorithm on Classification of Disk Hernia and Spondylolisthesis in Vertebral Column - Irma Handayani; Suprapto Suprapto (Universitas Budi Darma, 2023)
Good spinal health is needed to carry out daily activities. Trauma to the vertebral column can affect the spinal cord's ability to send and receive messages from the brain to the body's sensory and motor control systems. Disk hernia and spondylolisthesis are examples of pathology of the vertebral column. Research on pathology or damage to bones and joints of the skeletal system is rare. Whereas the classification system can be used by radiologists as a